Digitalisation and the church – A corporeal understanding of church and the influence of technology - Potgieter, Annette (Stellenbosch theological journal, 2019)
We live in a digital era, where connection and connectivity move away from physical presence, but find shape in online communities and forums. This trend extends from the secular world into the religious experience, as can be seen from examples such as E-kerk (E-Church). The body is a vehicle through which Paul defines the church and the medium through which Christians live a new life in Christ. Virtual communities, however, lack bodily presence and thus the tactile experience of the Lord’s Supper and the communal aspects of baptism. This raises the question whether it is possible for an individual to participate online in the body of Christ and if so, how?